Albert R Heilig, Ordinances of the City of Tacoma, Washington Page, at 334, Ordinance no. 134, § 1 (1892) - (:unkn) unknown (My University, 1892)
All persons (except police officers as aforesaid) who shall draw, exhibit or attempt to use any deadly weapon upon, to or against another person, in said city with intent to do bodily injury to such person; and All persons (except peace officers as aforesaid and persons practicing at target shooting in a shooting gallery duly licensed) who shall, within the city limits, fire off or discharge any gun, pistol or fire arm of any kind, or bomb, shall be deemed and are disorderly persons, and guilty of a misdemeanor.
Keywords: BRANDISHING; CARRY - CONCEALED; TAX - DEALERS